Comparative in vitro antioxidant activity of ethanol extracts of Vernonia amygdalina and Annona muricata leaves - Usunomena, Usunobun; Ewaen, Egharevba M.; Kevin, Ehiosun (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
In this work, in vitro antioxidant activities of ethanol extracts of Vernonia amygdalina (VAE) and Annona muricata (AME) leaves were comparatively evaluated using reducing power, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, hydrogen peroxide (H2O2) and superoxide anion radical scavenging assays as well as their inhibition concentration (IC50). The results showed that at maximum concentration (0.8mg/ml) on DPPH, percentage inhibition by ethanol leaf extracts of Vernonia amygdalina and Annona muricata were 81.13% and 76.77% respectively while ascorbic acid had 89.53% inhibition with IC50 values of 0.38, 0.41, and 0.34mg/ml respectively. The percentage inhibition of ethanol leaf extracts of Vernonia amygdalina and Annona muricata on H2O2 was also at the maximum concentration of 0.8mg/ml which were 78.30% and 80.14% respectively while ascorbic acid, the standard had 85.86% inhibition with IC50 values of 0.42, 0.41, and 0.36mg/ml respectively. Against superoxide anion radical, the maximum % inhibition was 65.36% for Vernonia amygdalina, 67.97% for Annona muricata and 83.79% for ascorbic acid, with IC50 values of 0.55, 0.50, and 0.37mg/ml respectively. In conclusion, Vernonia amygdalina and Annona muricata leaves possess antioxidant properties probably due to presence of bioactive compounds such as flavonoids, saponins, tannins and alkaloids which have the ability to scavenge free radicals that causes oxidative stress.